New Work: Sovereignty in the Postdigital Age Turning Point for Entrepreneurs, HR Professionals, Coaches and Employees - Berend, Benjamin; Brohm-Badry, Michaela (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
The essential introduces the New Work idea, the core of which is to pursue work that one "really, really wants". This approach is updated with regard to the three areas of individual, organization and society. Special consideration is given to findings from positive psychology and strength-oriented organizational research. With reference to examples and scientific findings, innovative working time models, organizational forms and management practices are presented. Finally, New Work is discussed in the context of progressive social ideas such as basic income, breathing life courses and post-growth. The content Digitization and post-digitization "Digital Athens" - Where is Digitization Leading? New Work I: The individual level New Work II: The organizational level New Work III: Work in the 21st century The target groups Entrepreneurs, employees, managers, economists, philosophers, coaches, trainers, politicians, educators Students and lecturers of education, economics and sociology The authors Dr Benjamin Berend is a research associate at the Chair of Learning and Instruction at the University of Trier. He is a founding member of the German Society for Positive Psychological Research (DGPPF). Prof. Dr. Michaela Brohm-Badry holds the Chair of Learning and Instruction at the University of Trier. She is President of the DGPPF. The translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content.
Digitalisation and post-digitalisation -- "Digital Athens" - Where does digitalisation lead? -- New Work I: The individual level -- New Work II: The organisational level -- New Work III: Work in the 21st century.
Keywords: Psychology, Industrial; Personnel management; Psychological consultation; Psychology; Work and Organizational Psychology; Human Resource Management; Consulting; Behavioral Sciences and Psychology